SYNTHESIS, CHARACTERIZATION AND APPLICATION OF SILVER-NANOPARTICLES-EMBEDDED ALKYD RESINS DERIVED FROM JATROPHA SEED OIL (FUDMA JOURNAL OF SCIENCES, 2023)
This research was carried out to synthesise, characterise and evaluate the performance properties of silver-nanoparticles embedded alkyd resin as binder in surface coating. Locally available Jatropha Seed Oil (JSO) was successfully converted to alkyd resin by alcoholysis and polycondensation reactions. The oil was reacted with glycerol to form monoglyceride which react further with phthalic anhydride to form the alkyd resin (JSOR) as monitored titrimetrically. Silver nanoparticles (AgNPs) were also synthesized from silver benzoate solution (SBS) by in situ reduction method. The SBS was mixed with JSOR in toluene to form a homogeneous mixture which subsequently formed silver nanoparticles-embedded alkyd resin (AgNPs-JSOR). The formation of AgNPs-JSOR was confirmed by colour change, UV-visible spectrophotometry which showed a surface plasmon resonance at 455 nm and FTIR spectroscopy which revealed a stretching vibration of Ag-O bond at 696 cm-1. The antimicrobial activity of SBS, JSO, JSOR,  and AgNPs-JSOR were evaluated against different pathogenic bacteria and fungi: Escherichia coli, Salmonella typhi, Staphylococcus aureus Aspergillus flavus, Aspergillus fumigatus and Mucor species using the disc diffusion method. The appearance of higher zone of inhibition (20-25 mm) in AgNPs-JSOR clearly indicated a higher antibacterial and antifungal activity when compared to SBS, JSO and JSOR.  The performance characteristics of the JSOR and Ag-NPs-embedded alkyd resins as ingredients in surface coatings (paint) were further evaluated. The results obtained revealed that the paint films air-dried within few hours, showed good solvent resistance and excellent light fastness suggesting the potentiality of AgNP-JSOR as binder in antimicrobial surface coatings.
Keywords: Jatropha seed oil, Alkyd resin, Silver nanoparticles, Plasmon resonance, FTIR, Antimicrobial